2019
DOI: 10.3389/fimmu.2018.03146
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genetic Results for Primary Immunodeficiency Disorders in a Highly Consanguineous Population

Abstract: Objective: To present the genetic causes of patients with primary immune deficiencies (PIDs) in Kuwait between 2004 and 2017.Methods: The data was obtained from the Kuwait National Primary Immunodeficiency Disorders Registry. Genomic DNA from patients with clinical and immunological features of PID was sequenced using Sanger sequencing (SS), next generation sequencing (NGS) of targeted genes, whole exome sequencing (WES), and/or whole genome sequencing (WGS). Functional assays were utilized to assess the biolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 40 publications
0
23
0
Order By: Relevance
“…In highly consanguineous populations, AR PIDs represent 70-90% of cases (32,33). Interestingly-though the Russian population is very heterogeneous, with low numbers of consanguineous marriages (45 families, 1.9%)-AR genetic defects comprised 30% of all defects described in the cohort, with 40% of these being homozygous for the respective mutations.…”
Section: Discussionmentioning
confidence: 99%
“…In highly consanguineous populations, AR PIDs represent 70-90% of cases (32,33). Interestingly-though the Russian population is very heterogeneous, with low numbers of consanguineous marriages (45 families, 1.9%)-AR genetic defects comprised 30% of all defects described in the cohort, with 40% of these being homozygous for the respective mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Autoantibodies testing, nitro blue tetrazolium dye test (NBT) or dihydrorhodamine (DHR) and complement hemolytic activity (CH50/100) with specific complement component were done when needed using the standard techniques. Genetic testing was done as described previously (19).…”
Section: Methodsmentioning
confidence: 99%
“…They provided an invaluable source of information about the natural history and outcome of specific diseases and documented variabilities between different populations (1518). They have supported research on the genetic, molecular, and physiological basis of PID (19, 20). They can be used to support clinical trials and translational research to improve quality of care, quality of life, and survival.…”
Section: Introductionmentioning
confidence: 95%
“…(17.1%), Among patients molecular diagnosis was observed in 40.2% and parental consanguinity was recorded in 19.4%[34][35][36].During the last decade, other Asian PID cohorts have been reported containing fewer patients each. Al-Herz et al in 2019, published a registry report of 314 PID patients in Kuwait with the highest genetically solved rate of 69.1% with 78.0% paternal consanguinity (prevalence of PID 20.2 in 100000, predominantly antibody immunodeficiency of 17.8%)[37][38][39]. In 2013, Ehlayel et al have reported a single-center registry of 131 pediatric PID patients from Qatar with the lowest number of classical PID diseases and only 23.7% predominant antibody deficiency (prevalence of PID of 1.1 per 100000 children, genetic diagnosis of 36.6%, parental consanguinity of 61.1%)[40].…”
mentioning
confidence: 99%